(untitled) (Castilla. Estudios de Literatura, 2021)
The purpose of this text is to analyze Besar al detective (2015) by Elmer Mendoza, a novel that is identified as part of the US-Mexico Border literature, and the Mexican drug trafficking novel. This analysis focuses on examining the presence of structures and power relationships and forms of resistance that we find in the symbolic spaces that make up the novel. To analyze the work, we focus on concepts proposed by Michel Foucault, Pierre Bourdieu, and James Scott.